Ion channels: methods and protocols - Gamper, Nikita, Ed (Methods in molecular biology; 998, 2013)
Every cell in our bodies contains a great variety and number of permeability pathways for various organic and inorganic ions, water, metabolites, nutrients, and signalling molecules. Maintenance and precise control of gating within these pathways are fundamental principles of life as these underlie basic cellular functions such as communication, contractility, and metabolism. In Ion Channels: Methods and Protocols, Second Edition, experts in the field contribute chapters that focus on the strategies, approaches, methods, and protocols for studying a large family of proteins that form ionic channels in the plasma membrane and intracellular membranes of cells. Using practical examples from the cutting-edge current research, this volume will take a look back at the major methods and approaches that aided the progress toward the current understanding of ion channel function, structural design, and biological roles. The volume also aims to look forward and identify approaches that will lead us to future discoveries. Written in the highly successful Methods in Molecular Biology [trade mark] series format, chapters include introductions to their respective topics, lists of the necessary materials and reagents, step-by-step, readily reproducible laboratory protocols, and tips on troubleshooting and avoiding known pitfalls. Authoritative and cutting-edge, Ion Channels: Methods and Protocols, Second Edition will greatly assist researchers searching for specific methodology in studying ion channels on the path toward a greater understanding of these key biological features.